Identifikasi Tumbuhan Paku (Pteridophyta) Di Kawasan Taman Alun-Alun Kota Kisaran - Widya Fazirah Miniati Siagian; Cut Aulia Andini; Lidya Lili Paramita; Suci Rahmadani; Majesty Christine Tambunan; Erika Wulandari; Ailya Meiwa Azzura; Khairunnisa Manurung (PEDAGO BIOLOGI, 2026)
Ferns or Pteridophyta, are a group of vascular plants that play a significant role in ecosystems, particularly as plants that grow attached to other surfaces and as ground cover in various habitats. Although urban areas are often considered unfavorable for biodiversity, they can still serve as suitable habitats for ferns, provided there are host trees and humid microclimatic conditions. This study was conducted at the Kisaran City Square Park in Asahan Regency, North Sumatra Province, in May 2026. The research aimed to identify fern species, describe their morphological characteristics, and analyze their adaptations and ecological roles. Observations were carried out using an exploratory method across three stations representing different levels of shading: heavily shaded, semi-open, and relatively open. The study identified eight fern species, comprising seven epiphytic species and one terrestrial species. These species include Asplenium nidus, Drynaria quercifolia, Pyrrosia piloselloides, Pyrrosia lanceolata, Davallia denticulata, Nephrolepis cordifolia, Asplenium polyodon, and Marsilea crenata. The presence of large host trees was the primary factor influencing fern diversity in the area, as evidenced by the dominance of epiphytic species. These findings highlight the crucial role of urban green spaces in maintaining biodiversity and provide a reference for sustainable vegetation management in city parks.